Blending Modification Technology of Insulation Materials for Deep Sea Optoelectronic Composite Cables - Shuhong Xie; Zhenzhen Chen; Zhiyu Yan; Xingyu Qiu; Ming Hu; Chunfei Gu; Xindong Zhao; Kai Wang (Energies, 2024)
The insulation layer of deep-sea optoelectronic composite cables in direct contact with high-pressure and highly corrosive seawater is required for excellent water resistance, environmental stress cracking resistance (ESCR), and the ability to withstand high DC voltage. Although high-density polyethylene (HDPE) displays remarkable water resistance, it lacks sufficient resistance to environmental stress cracking (ESCR). This article is based on a blend modification approach to mixing HDPE with different vinyl copolymer materials (cPE-A and cPE-B). The processing performance and mechanical properties of the materials are evaluated through rheological and mechanical testing. The materials’ durability in working environments is assessed through ESCR tests and water resistance experiments. Ultimately, the direct current electrical performance of the materials is evaluated through tests measuring space charge distribution, direct current resistivity, and direct current breakdown strength. The results indicate that, in the polyethylene blend system, the rheological properties and ESCR characteristics of HDPE/cPE-A composite materials did not show significant improvement. Further incorporation of high melt index linear low-density polyethylene (LLDPE) material not only meets the requirements of extrusion processing but also exhibits a notable enhancement in ESCR performance. Meanwhile, copolymerized polyethylene cPE-B, with a more complex structure, proves effective in toughening HDPE materials. The material’s hardness significantly decreases, and when incorporating cPE-B at a level exceeding 20 phr, the composite materials achieve excellent ESCR performance. In a simulated seawater environment at 50 MPa, the water permeability of all co-modified composite materials remained below 0.16% after 120 h. The spatial charge distribution and direct current resistivity characteristics of the HDPE, cPE-A, and LLDPE composite systems surpassed those of the HDPE/cPE-B materials. However, the HDPE/cPE-B composite system exhibited superior dielectric strength. The application of composite materials in deep-sea electro–optical composite cables is highly promising.